Kepastian Hukum Sema Nomor 2 Tahun 2023 Terhadap Pencatatan Perkawinan Antar-Agama Dalam Bingkai Kebhinnekaan Indonesia - Fenecia, Evelyn; Agustini, Shenti; Fitri, Winda (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Religious diversity in Indonesia has led to the practice of interfaith marriages, resulting in legal uncertainty. On July 17, 2023, the Supreme Court issued Circular Letter No. 2 of 2023 (SEMA 2/2023) to provide guidance to judges on adjudicating requests for the registration of interfaith marriages.Purposes of the Research: This study aims to analyze the implementation of SEMA No. 2 of 2023 concerning the registration of interfaith marriages within the framework of Bhinneka Tunggal Ika in Indonesia.Methods of the Research: The legal research method used is normative/doctrinal, with a qualitative research approach that includes legislative analysis of relevant regulations and conceptual analysis using legal theories related to the study.Results of the Research: The study reveals that SEMA 2/2023 provides legal certainty consistent with Indonesia's religious diversity and the Bhinneka Tunggal Ika motto. However, some judges continue to approve requests for the registration of interfaith marriages even after the issuance of SEMA, as evidenced by Decision No. 423/Pdt.P/2023/PN Jkt.Utr dated August 8, 2023. Thus, SEMA 2/2023 is insufficient to address the legal uncertainty surrounding interfaith marriages in Indonesia, despite its alignment with the spirit of Bhinneka Tunggal Ika. Legal harmonization across various regulations is needed to achieve the desired legal certainty.